Contribution of arbuscular mycorrhiza and exoenzymes to nitrogen acquisition of sorghum under drought - Munene, Rosepiah; Mustafa, Osman; Loftus, Sara; Banfield, Callum C.; Rötter, Reimund P.; Bore, Ezekiel K.; Mweu, Benard; Mganga, Kevin Z.; Otieno, Dennis O.; Ahmed, Mutez A.; Dippold, Michaela A. (Frontiers in Plant Science, 2025)
IntroductionFor low-fertile and degraded soils of sub-Saharan Africa, nitrogen (N) is often the most growth-limiting factor restricting crop yields. The often-suggested exploitation of advantageous rhizosphere traits such as enzyme secretion and/or the symbiosis with arbuscular mycorrhizal fungi (AMF) remains to be validated as a potential strategy to overcome N limitation, especially when N deficiency co-occurs with further abiotic stresses such as water scarcity.MethodsThree sorghum genotypes were cultivated in soil mesocosms with a root-exclusion compartment, where only AMF could scavenge for nutrients under drought and optimal conditions. Plant carbon (C) investment into the rhizosphere and N uptake were tracked by 15N application coupled with 13CO2 labelingResultsUnder drought, uptake of mineral 15N by AMF from the root-exclusion compartment increased 4–12 times compared to well-watered conditions. In addition, water stress enhanced below-ground allocation of recently assimilated C into microbial biomass. Drought reduced the enzymatic potential (Vmax) of chitinase while increasing leucine aminopeptidase (LAP) activity. This suggests that N acquisition via protein mineralization in soil was relatively enhanced compared to that of chitin following moisture limitation. LAP substrate affinity (Km) was reduced by drought compared to that of chitinase with genotype-specific shifts in the rhizosphere enzyme systems observed.ConclusionOur findings suggest that below-ground C allocation activated AMF symbiosis and its associated microbiome. This not only led to a shift in enzyme-driven exploitation of distinct organic N sources but also induced a strong increase in AMF-based mineral N acquisition from the mycosphere. This trait plasticity in response to drought may be harnessed to stabilize food production from low-fertile soil under the increasingly negative impacts of droughts due to climate change.